Design, construction and experimental performance of a nonlinear energy sink in mitigating multi-modal vibrations. (12th May 2020) - Dekemele, Kevin; Van Torre, Patrick; Loccufier, Mia
Abstract: To passively reduce the vibration energy in mechanical systems under shock load, nonlinear energy sinks (NES) can be locally attached, serving as vibration absorbers. The NES is an alternative to the standard tuned-mass-damper (TMD). While the TMD has a linear connecting spring, the NES has a nonlinear one. As a consequence, the NES has an energy dependent natural frequency. Because of this property, the NES is able to mitigate multi-modal transient vibrations sequentially from high to low frequency through a resonance capture cascade (RCC). This is a major advantage over the TMD, which is tuned only to reduce vibrations in a narrow frequency band, typically a single mode. Recently, three performance measures for the NES were derived, 1) The energy dissipation, the amount of total vibration energy dissipated by the NES. 2) The pumping time that estimates the time required for the NES to absorb a single frequency and 3) the cascading time, estimating the time the NES engages in RCC, absorbing all the modal frequencies. The novelty of these measures is that they only require the knowledge of the system's parameters. In this research, a complete implementation of a NES is presented, from design and practical realization, to verifying the performance measures experimentally. The performance measures thus allow to predict experimental performance of the NES without simulations or experiments, opposite to what literature does. The NES is constructed with a novel design methodology. This methodology allows for tailor made purely nonlinear stiffness. The NES is placed on a frame representing a scale model single-story building, to validate the single-mode performance. To obtain resonance cascading, a second story is added to obtain a two-mode dominant vibrating structure. The cascading time is predicted and confirmed by the experiments. The experiments agree well with both simulations and predictions regarding performance. This work validates the ease of use of the performance measures and their ability to predict experimental performance of a NES mitigating multi-modal vibrations. Highlights: A novel nonlinear energy sink (NES) design was proposed with cubic stiffness. The NES design was realized and identified. NES Performance was predicted and validated for an experimental two-frame structure. Resonance capture cascade duration was predicted and experimentally verified.